Supramolecular hydrogels for antimicrobial therapy - Hu, Benhui (2020)
The emergence of drug-resistant microbes has become a threat to global health, and microbial infections severely limit the use of healthcare materials. To achieve efficient antimicrobial therapy, supramolecular hydrogels demonstrate unprecedented advantages in medical applications due to the tunable and reversible nature of their supramolecular interactions and the capability of hydrogels to incorporate various therapeutic agents. Herein, antimicrobial hydrogels are categorized according to their inherent antimicrobial properties or based on their roles in encapsulating antimicrobial materials. Moreover, strategies to further enhance the antimicrobial efficacy of hydrogels are highlighted, such as the incorporation of antifouling agents or the enabling of response towards physiological cues. We envision that supramolecular hydrogels, in combination with modern medical technology and devices, will contribute to the development of efficient and safe systems for antimicrobial therapy.